Implementation of Digital Marketing Strategy in Increasing Company Competitiveness - Maulana, Arman (Yayasan Azka Hafidz Maulana, 2023)
This research discusses the implementation of digital marketing strategies and their impact on company competitiveness in the digital era. Digital marketing is considered a critical element in the business strategy of modern companies seeking to utilize information technology and the internet. This research discusses the background to the shift in consumer behavior to online platforms and the role of digital marketing in exploiting this opportunity. The research method used is documentation study, with a focus on financial data analysis, digital marketing campaign archives, and related literature. The research results show that digital marketing has the potential to increase a company's visibility online, expand market coverage, and increase consumer engagement. Data analysis and use of the right digital marketing techniques can increase conversion rates, turning prospects into active customers. Digital marketing also allows companies to measure campaign performance in real-time, provide insight into strategy effectiveness, and measure Return on Investment (ROI) more accurately. Additionally, a thoughtful digital marketing strategy helps build and strengthen a company's brand image, differentiating it from competitors in the market. In conclusion, digital marketing is not only a tool to increase sales, but also a strategic approach that forms the basis of a company's sustainability and competitiveness in this digital era. This research provides an in-depth look at the role of digital marketing in facing challenges and exploiting opportunities in the ever-evolving business world.